2009
DOI: 10.1073/pnas.0903672106
|View full text |Cite
|
Sign up to set email alerts
|

Revising the recent evolutionary history of equids using ancient DNA

Abstract: The rich fossil record of the family Equidae (Mammalia: Perissodactyla) over the past 55 MY has made it an icon for the patterns and processes of macroevolution. Despite this, many aspects of equid phylogenetic relationships and taxonomy remain unresolved. Recent genetic analyses of extinct equids have revealed unexpected evolutionary patterns and a need for major revisions at the generic, subgeneric, and species levels. To investigate this issue we examine 35 ancient equid specimens from four geographic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
138
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 52 publications
18
138
3
4
Order By: Relevance
“…It is therefore not entirely surprising that not all wild horses shared the bay-dun or black-dun phenotypes. Moreover, previous studies suggested that morphological-and genetic-variability was much larger in Pleistocene animal populations compared with their modern counterparts (30)(31)(32), and it is likely that this increased variability extended to color phenotypes as well. However, the overall picture still supports the notion that artificial selection was the driving force behind the rapid increase of coat-color variation in domestic animals and resulting in their remarkable modern variability.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not entirely surprising that not all wild horses shared the bay-dun or black-dun phenotypes. Moreover, previous studies suggested that morphological-and genetic-variability was much larger in Pleistocene animal populations compared with their modern counterparts (30)(31)(32), and it is likely that this increased variability extended to color phenotypes as well. However, the overall picture still supports the notion that artificial selection was the driving force behind the rapid increase of coat-color variation in domestic animals and resulting in their remarkable modern variability.…”
Section: Discussionmentioning
confidence: 99%
“…We drilled and extracted the tooth sample which we named P2_Leceia (415 mg) and for comparison a second tooth P1_Porto (a left M/2 collected from Porto das Carretas, a Chalcolithic site in the south of Portugal, near the Guadiana river, and dated to around the same time as the Leceia sample, the second half of the third millennium BC) 185e332 mg were obtained from three extractions by a silica-based extraction protocol as in Orlando et al (2009) with appropriate extraction controls in an ancient DNA laboratory at the Centre for GeoGenetics, Copenhagen, Denmark. We then built the DNA extractions into indexed blunt-end libraries using the NEBNext DNA Library Prep Master Mix set for 454 (Biolabs,ref:E6070s) and amplified the libraries as in Vilstrup et al (2013).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…28, 51, 225) and even for the manufacture of shields for war (Antunes, 2006), supporting venatory activities, and also to prevent the destruction of crops by this herd living animal. The correlation between E. hydruntinus and the "zebro", though attractive, has been rejected by ancient DNA analyses that assigned the remains purported to have been the last representative of this species, to donkeys (Orlando et al, 2009). Therefore, the "zebro" were most likely domestic donkeys (E. asinus) turned feral, a possibility proposed by C. Liesau, during several stages of the historic record, related to epidemic diseases, which conduced to the abandonment of the fields (pers.…”
Section: Introduction: the Past Presence Of Equids In The Iberian Penmentioning
confidence: 99%
“…For the infinitely dated samples, the 95% CIs include the range 30,000-80,000 years, and the weight of the sample density is concentrated around 52,000 years. A further calibration was incorporated at the time of divergence between E. asinus, and the remaining lineages: We used a lognormal prior sampling between 1.0 and 5.5 myrs; these confidence intervals incorporate both the fossil record age estimates [57][58][59] and previous divergence estimates based on molecular data 60 . The results of the tip-dating analysis are shown in Supplementary Table S7. …”
Section: Primer Designmentioning
confidence: 99%